TI_GERICHTE 15.2015.42 vom 24. Juni 2016 , Ricorso contro un precetto esecutivo ritenuto manifestamente abusivo - TI Tribunale d'appello (2016)
Ricorso contro un precetto esecutivo ritenuto manifestamente abusivo